The catalytic properties of Fe-S cluster containing enzymes - Islam, S (2017)
Many enzymes contain iron- sulfur (Fe-S) clusters which have a huge impact on their catalytic properties. These clusters may form part of the active site or form an electron relay system from the surface of the protein to the active site. Protein film electrochemistry (PFE) was utilized to elucidate the properties of some Fe-S cluster enzymes, namely, Hyd-1(a hydrogenase with an Fe-S electron relay), PceA (a reductive dehalogenase containing Fe-S clusters to facilitate electron transfer with redox partner) and CODH ICh and CODH IICh (carbon monoxide dehydrogenases with Fe-S electron relay systems and Ni-incorporated Fe-S clusters as active sites). The role of a proline residue at the active site in Hyd-1 was investigated and it was concluded that some local instability and adverse effect on H2 activation were introduced upon replacement of proline with an alanine residue. The PceA dehalogenase was studied with PFE in terms of their interactions with various substrates and inhibitors. Furthermore, a method for performing 'film correction' for liquid substrates as that of the dehalogenase was established. Aspects of the catalytic cycle and effects of oxygen (O2), peroxide (H2O2) and hydroxylamine (NH2OH), a nitrogen-containing peroxide analogue on CODH ICh and CODH IICh were investigated with PFE. Finally, Electrochemical Impedance Spectroscopy (EIS), a technique involving application of alternating current (AC), was added to the portfolio was PFE techniques to compare CpI and CrHydA1 (hydrogenases with and without Fe-S electron relay system, respectively) in terms of time-dependent and time-independent processes within them. A novel term, exchange catalytic rate, for expressing inherent proficiency of the enzyme at zero-current potential was proposed and quantified. A means for measuring electroactive coverage and theoretical turnover during catalysis in PFE experiments was developed.